Drug-eluting bead transarterial chemoembolization (TACE) vs conventional TACE in treating hepatocellular carcinoma patients with multiple conventional TACE treatments history: A comparison of efficacy and safety - Li, Hui (Medicine (Baltimore), 2019)
This study aimed to compare the efficacy and safety of drug-eluting bead transarterial chemoembolization (DEB-TACE) vs conventional TACE (cTACE) in hepatocellular carcinoma (HCC) patients with multiple cTACE treatments history. Eighty-one HCC patients with multiple cTACE treatments history who underwent DEB-TACE (N = 42) and cTACE treatment (N = 39) were included in this retrospective cohort study and allocated to DEB-TACE and cTACE groups accordingly. Multiple cTACE treatments history was defined as history of three or more cycles cTACE treatments. Then treatment responses were assessed according to the criteria of modified Response Evaluation Criteria in Solid Tumors (mRECIST), and progression free survival (PFS), as well as overall survival (OS), was calculated. In addition, adverse events and liver function related indexes were recorded. Complete response (P = .167) was of no difference while objective response rate (ORR) (P = .003) was increased in DEB-TACE group compared with cTACE group. Patients in DEB-TACE group presented with more favorable PFS (P = .028) and OS (P = .037) compared with cTACE group. Further analysis revealed that DEB-TACE (vs cTACE) was an independent predictive factor for better ORR (P = .001), PFS (P = .006) and OS (P = .001). The albumin (ALB) level at first month after treatment was elevated (P = .015) while the other liver function indexes levels did not vary (all P > .05) in DEB-TACE group compared with cTACE group. The incidences of pain (P = .327), fever (P = .171) and nausea/vomiting (P = .400) during hospitalization were similar between the 2 groups. DEB-TACE is more efficient and equally tolerant compared with cTACE in HCC patients with multiple cTACE treatments history.